Penetapan Kadar Zink Pada Sediaan Farmasi Dengan Metode Kompleksometri dan Spektrofotometri Serapan Atom - Dwi Dinni Aulia Bakhtra; Zulharmita Zulharmita; Valeria Pramudita (STIFARM Padang, 2015)
Research on the determination of zinc in pharmaceutical preparations have been carried out by complexometry and atomic absorption spectrophotometry. This research aims to determine and compare the levels of zinc in pharmaceutical preparations by complexometry method and atomic absorption spectrophotometry. Samples used zinc tablets were Zinkid® (PT. Indofarma), Zincare® (PT. Kalbe Farma) and Zinc generic tablets (PT. Kimia Farma). Zinc calibration curve at wavelength 213.9 nm used standard solution ZnSO4.7 H2O have correlation coefficient 0.9937 and linear regression equation y = 0.1124 + 0.4403x. Standard deviation 0.088. Detection limit 0.5996 mg/kg and quantitation limit 1.9986 mg/kg. The assay of zinc by complexometry method trademarks Zinkid® obtained zinc content 3.57 %, Zincare® 6.12 % and Zinc generic 3.68 %. While the method of atomic absorption spectrophotometry Zinkid® obtained zinc content 3.64 %, Zincare® 6.19 % and Zinc generic 3.72 %. Result of statistical analysis using t-test, it could be concluded that the method complexometry and atomic absorption spectrophotometry for the determination of zinc in pharmaceutical preparations dosage levels were not significantly different (sig.>0.05).